Afterdischarges in Myasthenia Gravis - Yang, Li; Guo, Shougang; Chen, Xiuying (Frontiers in Neurology, 2021)
Introduction: This study aimed to analyze the clinical features of myasthenia gravis (MG) in combination with the afterdischarges and compare the characteristics of afterdischarges in MG with different serum antibodies. Methods: Ninety-two patients with MG were analyzed retrospectively. The afterdischarges were investigated using motor nerve conduction examination, F-wave examination, and repetitive nerve stimulation (RNS). Results: Afterdischarges were observed after the M wave in 14 of 92 patients. Three of these 14 patients tested positive for the muscle-specific tyrosine kinase antibody (MuSK-Ab), and 11 patients tested positive for the acetylcholine receptor antibody (AchR-Ab). The characteristics of the afterdischarges on RNS differed distinctly between the two antibody groups. The afterdischarges occurred on the first stimulation, but decreased on the second and subsequent stimulations in patients with MuSK-MG, while the afterdischarges continued to occur on each stimulation in patients with AchR-MG. Discussion: The characteristics of the afterdischarges on RNS enabled easy identification of their synaptic or neurogenic nature.